Altered 3D Structure of Human Tryptophan Hydroxylase-2 Caused by Change in the amino acid 341: In Silico Analysis - Castaño Casas, Juan Pablo; Barona, Juan Sebastián Pérez; Betancourth, Flavio Edgar Cerón; Salazar, Doris Haydee Rosero (Journal of Morphological Sciences, 2018)
Introduction Neuropsychiatric syndromes have an important connection with disorders in the regulation of serotonin, with human tryptophan hydroxylase-2 being one of the related biosynthetic enzymes of this neurotransmitter. Evidence-based genetic studies suggest a possible involvement of this enzyme in neuropsychiatric disorders caused by abnormalities in the synthesis and regulation of serotonin.Objective To analyze the structural effects of single nucleotide polymorphism (SNP) in the enzyme tryptophan hydroxylase-2 and the changes that lead to functional alterations.Materials and Methods In this study, we performed an in silico analysis of SNPs associated with abnormal folding of the tryptophan hydroxylase-2 protein. Different programs were used to identify amino acid changes evidencing pathogenic effects and possible functional impairments.Results A change in the amino acid 341 (lysine [L]for phenylalanine [F]) (L341F) of the protein chain affects the total enthalpy of the protein. The enthalpy turned positive due to the energy required for the amino acid to return to its original condition. The protein function is also affected negatively because of the altered structured.Conclusion The change in the L341F leads to serious structural defects in the tryptophan hydroxylase-2. Those defects can be further related with functional instability and associated to the etiology of neuropsychiatric diseases.
Keywords: polymorphism; serotonin; tryptophan hydroxylase; SNPs; amino acid